Hamiltonian paths passing through matchings in hypercubes with faulty edges - Shenyang Zhao; Fan Wang (AIMS Mathematics)
Chen considered the existence of a Hamiltonian cycle containing a matching and avoiding some edges in an $ n $-cube $ Q_n $. In this paper, we considered the existence of a Hamiltonian path and obtained the following result. For $ n≥4 $, let $ M $ be a matching of $ Q_n $, and let $ F $ be a set of edges in $ Q_n-M $ with $ |M\cup F|≤2n-6 $. Let $ x $ and $ y $ be two vertices of $ Q_n $ with different parities satisfying $ xy\notin M $. If all vertices in $ Q_n-F $ have a degree of at least $ 2 $, then there exists a Hamiltonian path joining $ x $ and $ y $ passing through $ M $ in $ Q_n-F $, with the exception of two cases: (1) there exist two neighbors $ v $ and $ t $ of $ x $ (or $ y $) satisfying $ d_{Q_n-F}(v) = 2 $ and $ xt\in M $ (or $ yt\in M $); (2) there exists a path $ xvuy $ of length 3 satisfying $ d_{Q_n-F}(v) = 2 $ and $ uy\in M $ or $ d_{Q_n-F}(u) = 2 $ and $ xv\in M $.